Pedikulosis Kapitis Disertai Ektima pada Seorang Perempuan Usia 17 Tahun - Puan Nassya Amalia Islamy; Mohamad Mimbar Topik (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pediculosis capitis is an infestation of head lice Pediculus humanus capitis that live on the scalp and suck blood as a source of nutrition. Transmission occurs through direct contact or sharing personal items, especially in environments with poor sanitation. Risk factors include age, population density, personal hygiene, and socioeconomic status. Symptoms include severe itching due to a reaction to the saliva of the lice, which can cause excoriation, irritation, and secondary infections such as pyoderma. In this report, a 17-year-old girl complained of scabs, pain, heat, and itching on the head and neck. Lice and lice eggs were found, as well as ecthyma lesions in the form of pustules, yellow crusts, and excoriations in the occipital area and back of the neck. The therapy given was a combination of drug and non-drug treatment. The evaluation results showed improvement in symptoms. This case emphasizes the importance of early diagnosis and comprehensive management to prevent reinfection.